Revolutionizing Educational Communication Psychology in the Digital Era - Jannah, Rafidatul; Muhammad Ansar; Zameliuk, Mariia (Feedback International Journal of Communication, 2024)
In the digital era, educational communication psychology plays a pivotal role in shaping interactions among teachers, students, and parents. This study addresses the critical need to understand these dynamics, identify challenges, and explore the potential of technology to enhance learning effectiveness. A library research method was employed, reviewing relevant academic literature on educational communication, psychology, and digital learning to identify patterns, challenges, and opportunities in the digital context. The findings reveal that while technology enhances student engagement through innovative tools, significant barriers, including the digital divide and lack of digital literacy, persist. Psychological theories, particularly those concerning motivation and behavior, are integral to understanding student dynamics in digital education. The study highlights the importance of integrating psychological principles with technology to address challenges such as cognitive overload and disengagement. Effective and inclusive communication strategies must prioritize socio-emotional learning and address inequalities to foster a sustainable learning environment. Education in the digital era requires simultaneous attention to psychological and technological aspects. Institutions must adopt holistic strategies that leverage technology while addressing psychological needs to create equitable and effective learning experiences.